The Tracks of Datuk Malik Ibrahim the Pioneer of the Spread of Islam in Banyuwangi - Mahfud; Dwi, Lidia; Mahendra, Maulana Iqbal; Supri, Gea (CV. Sekawan Siji, 2025)
Datuk Malik Ibrahim is one of the famous figures in the history of the spread of Islam in Indonesia, especially in East Java, including Banyuwangi. He is known as a great cleric who had a great influence in the spread of Islam in Java in the 15th and 16th centuries. The process of spreading Islam carried out by Datuk Malik Ibrahim was part of the da'wah movement that took place in Java at that time, which was driven by various social, political, and cultural factors. Datuk Malik Ibrahim is thought to have been born in an area in Minangkabau, Sumatra, but he is better known as an active cleric in East Java. One of the places that was greatly influenced by his da'wah was Banyuwangi, an area on the eastern tip of Java. In Banyuwangi, Datuk Malik Ibrahim was known as one of the pioneers in establishing Islamic boarding schools and carrying out peaceful Islamic da'wah that respected local culture. At that time, the majority of the Banyuwangi community was Hindu-Buddhist, so the spread of Islam had to be carried out with a wise approach and prioritized tolerance. Datuk Malik Ibrahim understood the importance of a cultural approach in da'wah. He not only taught Islam through lectures or teachings at Islamic boarding schools, but also through inclusive social interactions that prioritized local wisdom. This approach made it easier for the local community to accept Islamic teachings. As a cleric, Datuk Malik Ibrahim was known as a humble and compassionate figure. One way he spread Islam was by establishing Islamic educational institutions, such as Islamic boarding schools. The Islamic boarding schools he founded became educational centers that taught religious values, morality, and wisdom. In addition, he also taught knowledge including fiqh, tafsir, hadith, and Arabic. The spread of Islam carried out by Datuk Malik Ibrahim in Banyuwangi was also in line with the influence of Islamic kingdoms that developed in Java at that time, such as the Demak Sultanate and the Giri Sultanate. His closeness to local rulers, especially the kings who ruled in the Banyuwangi region, provided support for his Islamic preaching. With this support, Islamic teachings increasingly found a place among the Banyuwangi community. One of the characteristics of the preaching carried out by Datuk Malik Ibrahim is his success in integrating Islamic teachings with local culture. He did not force drastic changes to people's habits, but rather chose an approach that was harmonious with existing customs and traditions. This made the spread of Islam in Banyuwangi run more smoothly and was accepted by various levels of society. As a figure who was dedicated to spreading Islam, Datuk Malik Ibrahim left a very valuable legacy for the development of Islam in East Java, especially in Banyuwangi. His teachings and messages of preaching were continued by his students, who later became great scholars in the region. The legacy of Islamic education that he built in Banyuwangi continues to grow to this day, making him one of the important figures in the history of the spread of Islam in Indonesia. This study uses heuristic historical research, interpretation, historiography, and criticism. The tomb of Datuk Malik Ibrahim located in Banyuwangi is one of the important religious tourism objects and has high historical value. As one of the sites visited by many tourists, both for spiritual and historical purposes, the management of this place is very important to ensure its sustainability as a safe, comfortable tourist destination that can provide benefits to the surrounding community. This plan aims to design a sustainable management program with an approach that involves the community, cultural preservation, and local economic development. The tomb of Datuk Malik Ibrahim is located in Lateng, Banyuwangi Regency, East Java Province. The tomb of Datuk is one of the tombs that has a history of how Islam developed in Banyuwangi.